Algal biofilm-assisted microbial fuel cell to enhance domestic wastewater treatment: Nutrient, organics removal and bioenergy production - Yang, Zhigang; Pei, Haiyan; Hou, Qingjie; Jiang, Liqun; Zhang, Lijie; Nie, Changliang (Chemical engineering journal (Lausanne, Switzerland : 1996), 2018)
•Contaminant removal in the ABMFC was better than that in the MFC or AB alone.•62.93mW·m−2 power density and 6.26mg·L−1·d−1 lipid productivity were obtained.•Deltaproteobacteria grew well with algal biofilm but Betaproteobacteria did not.•Bioenergy of 0.094kWhperm3 of wastewater was obtained in continuous operation. An algae biofilm microbial fuel cell (ABMFC) was established by integrating an algal biofilm (AB) with a microbial fuel cell (MFC) to facilitate the system’s operation for nutrient removal and bioenergy generation. In batch mode, the removal efficiencies of TN, TP and COD in the ABMFC reached 96.0%, 91.5% and 80.2%, respectively, which performed much better than MFC or AB alone. The highest power density of the ABMFC (62.93mW·m−2) was 18% higher than that of the MFC (52.33mW·m−2), and a lipid productivity of 6.26mg·L−1·d−1 could be obtained simultaneously. High-throughput sequencing revealed that Chlorobia and Deltaproteobacteria grew well in the symbiotic ABMFC system. Betaproteobacteria, versatile in organic pollutant degradation, was inhibited by algal biofilm; it may be due to the nutrients competitions between algae and Betaproteobacteria. It was proved that the ABMFC system was able to handle real, complex, variable wastewater in the continuous flow trials and a total energy of 0.094kWh·perm3 of wastewater was obtained in the process. This study not only developed a wastewater treatment and energy recovery method but also explored a better understanding of the mechanisms for the algae-bacteria system.